Asgard Corrugated Box a production systems study - Mendoza, Ma. Eleanor; Ong. Michael; Pascual, Kathleen (Diliman, Quezon City College of Engineering, 1992)
Asgard Corrugated Box Manufacturing Corporation is engaged in the buying of paper rolls and converting them into corrugated boxes. The study conducted at the plant site in Novaliches shows that the plant is operating below its actual capacity resulting in underutilization of the company's labor resources and its machines and equipment. Findings show that underutilization is caused by: 1.Frequent breakdown of boiler 2.Lack of competent sales personnel. 3.Limited working capital. 4. inefficient production planning system. 5. Lack of raw materials. The study proponents came out with the following recommendations: For short term: 1. retain the old boiler until the company has enough funds to buy a new one 2. Here additional salesmen - to increase sales to increase utilization of the labor and its machines 3. cope up with present credit loan policies imposed by the suppliers 4. Maximize the available working capital. For long term: 1. Buy a New boiler 2. Continue hiring of salesmen until production reaches full capacity 3. Look for tie-up partner to solve the problem on limited working capital or do subcontracting to maximize its capacity.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Asgard Corrugated Box; Paper products; Production engineering